Understanding Emotional Intelligence Factors and Individual Commitment Towards Organizational Change - Norfadzilah, Abdul Razak (2011)
Emotional intelligence becomes increasingly valued in the workplaces in the future especially in managing change. It is one of the most important competencies for an individual to understand, own and other's emotions when change occurs at workplaces. Emotional intelligence enhances individual competencies and influences their job behavior as to commit to the changes.The objective of this study is to understand the relationship between emotional intelligence and commitment to change at individual perspectives. A survey was conducted among the 144 administrative staff in Universiti Utara Malaysia whom at present are facing changes within their organization. A questionnaire was distributed among the administrative staff in respond towards the emotional intelligence factors and commitment to change. The quantitative method was used to analyze the data collected from the respondent. The data collections then were analyzed and interpret in the Statistical Package for Social Sciences version 15. The analysis interpreted data to identify the correlation and significant of emotional intelligence which consists of four dimensions which self emotions appraisal, other emotions appraisal, use of emotions and regulate of emotions towards commitment to change.The correlation founds the emotional intelligence factors were significant and positive relationship towards commitment to change. However the correlation of self emotions appraisal indicates at low level (0.249) while the others factors at high level.Regression analysis differently shows that other emotions appraisal and regulate of emotions are significant with commitment to change while self emotions appraisal and use of emotions are not significant in this study. In this study, the results explained emotional intelligence factors accounts for an estimated 41% of the variation in commitment to change.